New tools and recommendations for a better management of harmful algal blooms under the European Marine Strategy Framework Directive - Sagarminaga, Yolanda; Garcés, Esther; Francé, Janja; Stern, Rowena; Revilla, Marta; Magaletti, Erika; Bresnan, Eileen; Tsirtsis, George; Jakobsen, Hans Henrik; Sampedro, Nagore; Reñé, Albert; Camp, Jordi; et al. (Frontiers in Ocean Sustainability, 2023)
Marine harmful algal blooms (HABs), caused by various aquatic microalgae, pose significant risks to ecosystems, some socio-economic activities and human health.Traditionally managed as a public health issue through reactive control measures such as beach closures, seafood trade bans or closure of mollusc production areas, the multifaceted linkages of HABs with environmental and socio-economic factors require more comprehensive ecosystem-based management approach tools to support policies.This study promotes a coordinated understanding and implementation of HAB assessment and management under the Marine Strategy Framework Directive (MSFD), targeting the achievement of Good Environmental Status (GES) in European marine waters. We introduce two novel tools: GES4HABs (GES for HABs) decision tree, and MAMBO (environMental mAtrix for the Management of BlOoms), a decision support matrix. These tools aim to streamline HABs reporting and prioritize resource allocation and management interventions. The GES4HABs decision tree defines a sequence of decision steps to identify HAB management strategies according to their state (evaluated against predefined baselines) and causes (anthropic or natural). MAMBO is proposed to address different HABs and their interaction with human and environmental pressures.The matrix utilizes two axes: natural trophic status and level of human influence, capturing major aspects such as nutrient supply. While acknowledging the limitations of this simplified framework, MAMBO categorizes marine regions into quadrants of varying management viability. Regions with high human influence and eutrophic conditions are identified as most suitable for effective management intervention, whereas regions with minimal or mixed human influence are deemed less amenable to active management. In addition, we explore and describe various indicators, monitoring methods and initiatives that may be relevant to support assessments of HAB status and associated pressures and impacts in the MSFD reporting. Finally, we provide some recommendations to promote the consideration of HABs in ecosystem-based management strategies, intensify efforts for harmonizing and defining best practices of analysis, monitoring and assessment methodologies, and foster international and crosssectoral coordination to optimize resources, efforts and roles.